284 Co-Creation in Action: Design and Implementation of a Studio to Increase Inclusion in Research - Stacey M. Gomes; Sarah J. Beal; Joseph Kiesler; Carley L. Riley; Monica J. Mitchell (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: The goal of theIntegrating Special Populations (ISP) Studiosis tointegrate communityvoice into research design and en hance diversity, equity, and inclusion in research, and disseminate findings in ways that improve health literacy and equity. METHODS/STUDY POPULATION: Based on the Vanderbilt Community Engagement Studio model, the ISP Studiowas designed through multiple phases, including Designand PilotStudioSessions. Stakeholders were diverse representatives of community and academic organizations serving special populations, as well asself-identified persons within special populations as defined by the NIH.Each phase of development and implementation of the Studio included an evaluation consisting of Likert scale and open-ended survey questions for process improvement and to integrate voices of the ISP community continuously. Demographic information and program outcomes were also collected via the evaluation survey. RESULTS/ANTICIPATED RESULTS: All Design Session (N=9) and Pilot Studio (N=10) participants indicated that the Design and Pilot were positive, relevant, bidirectionally useful, and fostered respect, trust, and inclusion. 100% of the panel strongly agreed the Studio met its goals and that the ISP Studios have potentialtobenefitspecial and under represented populations. Qualitative data and discussion on design will also be shared. Additi onaland relevant pointsincludepanelisttraining,compensation for community panelists, and ensuring accessibility. Evaluation outcomes from initial implementation of the ISP Studio will be discussed. DISCUSSION/SIGNIFICANCE: The ISP Studio is an innovative model that may increase engagement of special populations in the research process through co-creation and integration of lived experiences.It has the potential to improve research design, implementation, and impact.